Murder to Marriage: Love and the Evolution of The Killers - Tosha R. Taylor (Journal of Popular Romance Studies, 2018)
The Killers’ music crosses genres and seems to alternate between upholding or challenging the conventions of rock music. This is particularly evident in their depiction of romantic desire. Through their recording career, their work has undergone a dramatic shift in its engagement with love. Early songs often dealt with spurned male lovers who react violently to rejection, culminating in what is known as the band’s Murder Trilogy. However, their more recent work has departed from rock’s critically cited fixation with freedom and sexualized love to concern the struggles of prolonged relationships in which partners face the pressures of romantic disillusionment. Their evolution has conspicuous ties to frontman Brandon Flowers’ own marital and religious commitments. This article traces such thematic changes to investigate relationships between love, masculinities, and spirituality in rock music. Through close readings of The Killers’ music, with particular care for the influence of their frontman, the article uncovers the cohesive evolution of the theme of romance in their discography.